Porosity development in activated carbon from palm kernel and coconut shell by chemical activation method - Rahman, Md. Mokhlesur; Adil, Mohammad; Yusof, Alias Mohd (Research Journal of Chemistry and Environment, 2012)
Several series of activated carbons have been prepared by chemical activation with phosphoric acid from palm kernel and coconut shells to study the effect of preparation variables such as precursor, precursor size, pretreatment, impregnation condition and ratio and finally the carbonization temperature on specific surface area and pore distribution of the resulting active carbon. Both precursors showed similar N2 adsorption isotherms, an upward deviation at high relative pressure, revealing the presence of mesorpores when carbonized at 5000 C with H3PO4. The bigger hysteresis loop indicates higher mesoporosity in coconut shell derived carbon whereas palm kernel shell derived carbon showed a higher macroporosity nature Prolong sinking of the precursor in H3PO4 impregnation solution followed by carbonization at moderate temperature (450-500 0C) produces carbon of high surface area with a higher macroporosity. The lowering of precursor size favors micropore development and semi-drying of the impregnation chemical prior to carbonization diminishes the macroporosity to a great extent. Thus an appropriate choice of preparation variables enables us to produce high surface area of micro and mesoporous activated carbon.